Discovery of the second Asian Holocompsa species from China, and supplemental description of the male of H. debilis (Blattodea: Corydiidae: Euthyrrhaphinae). Issue 6 (1st November 2020) - Qiu, Lu; Wang, Zong-Qing; Che, Yan-Li
Summary: The second Asian Holocompsa species, Holocompsa zhangi n. sp ., is reported from Yunnan, China. This new species can be easily distinguished from Holocompsa debilis Walker, 1868, the only previously known Asian species, by the yellowish color on tegmina, the shape of wings, supra-anal plate, subgenital plate, and the detailed structures of the male genitalia. Supplemental description of H. debilis is given based on a male specimen from Yunnan, China. An identification key to the Holocompsa from Asia and a checklist of Holocompsa of the world are provided.